Physicochemical properties of chitosan/graphene oxide composite films and their effects on storage stability of palm-oil based margarine - Foong, Han Lyn; Tan, Chin Ping; Mohd Zawawi, Ruzniza; Zainal Abedin, Nur Hanani (Elsevier BV, 2021)
This study investigated the application of active packaging from chitosan (CS) incorporated with graphene oxide (GO) to maintain the quality and extend the storage life of palm-oil based margarine. Composite films containing various concentrations of CS (1.5 and 2.0%w/v) and GO (0, 0.5, 1.0, and 2.0%w/w CS) were produced using the solution casting method and were characterized regarding their mechanical, barrier, and antioxidant properties. For both concentrations of CS, the composite films with 2.0% GO exhibited significantly (p < 0.05) lower water vapor permeability and oxygen permeability by ~43 and ~55%, respectively. The transmittance of UV light was virtually undetectable in CSGO composites. In addition, the radical scavenging activity increased (p < 0.05) with the increasing GO concentration, as demonstrated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The changes in the peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) of the margarine samples were monitored for 30 d at 4 °C. The margarine sample that was wrapped with the CS1.5 GO2.0 film sample showed lower (p < 0.05) PV and TBARS values in comparison to the samples wrapped with CS1.5 and low-density polyethylene (LDPE) films. In conclusion, the CSGO composite film in this study shows great potential as an antioxidant food packaging material.